The role of novel programmed cell death in head and neck squamous cell carcinoma: from mechanisms to potential therapies - Xi, Yujie; Gao, Ling; Li, Shaming; Sun, Kai; Chen, Peishen; Cai, Zhen; Ren, Wenhao; Zhi, Keqian (Frontiers in Pharmacology, 2023)
Head and neck squamous cell carcinoma (HNSCC) is a common oral cancer with poor prognoses and no targeted therapeutic strategies currently available.Accumulating evidence has demonstrated that programmed cell death (PCD) is essential for the development of HNSCC as a second messenger. PCD can be divided into numerous different subroutines, in addition to two majorapart from two wellknown types of apoptosis and autophagy, novel programmed cell death (e.g. necroptosis, pyroptosis, ferroptosis, and NETosis) is also served as a key alternative in tumorigenesis. Cancer cells are not able to avoid all cell death types at once since different cell death subroutines with different regulatory pathways. Herein, we summarize the roles of novel programmed cell death in tumorigenesis and how we interpret molecular mechanisms to more potential therapies.